Nrf2-Heme oxygenase-1 modulates autophagy and inhibits apoptosis triggered by elevated glucose levels in renal tubule cells - Joo-Heon Kim; Kyeong Min Kim; Jin Uk Jeong; Jong Ho Shin; Jae Min Shin; Ki Tae Bang (The Korean Society of Nephrology, 2019)
Background : Autophagy is a highly balanced process in which lysosomes remove aged and damaged organelles and cellular proteins. Autophagy is essential to maintain homeostasis in the kidneys. Methods : Using human renal tubule cells HK-2, we assessed the impact of high glucose (HG) on autophagy. We also evaluated the capability of sulforaphane (SFN) to protect the HK-2 cells from HG-induced apoptosis by modulating autophagy. Results : SFN modulated autophagy and decreased apoptosis in the HK-2 cells that were cultured in 250 mM glucose medium for two days. The reactive oxygen species (ROS) levels increased, as expected, in the cells cultured in the 250 mM glucose medium. However, the SFN decreased the ROS levels in the HK-2 cells. The overexpression of heme oxygenase-1 (HO-1) by SFN decreased the expression of LC3 and beclin-1. LC3 and beclin-1 were involved in the downregulation of caspase-3 that was observed in the HG-induced cells. Conclusion : The activation of nuclear factor E2-related factor 2 (Nrf2)-HO-1 inhibited ROS expression and subsequently attenuated autophagy and cell apoptosis after HG injury was decreased. HG injury led to the activation of autophagy and HO-1 in order to combat oxidative stress and protect against cell apoptosis. Therefore, HO-1 activation can prevent ROS development and oxidative stress during HG injury, which considerably decreases autophagy and apoptosis.